Short-term intensified training temporarily impairs mitochondrial respiratory capacity in elite endurance athletes - Cardinale, D. A.; Gejl, K. D.; Petersen, K. G.; Nielsen, J.; Ørtenblad, N.; Larsen, F. J. (Journal of Applied Physiology, 2021)
The maintenance of healthy and functional mitochondria is the result of a complex mitochondrial turnover and herein quality-control program that includes both mitochondrial biogenesis and autophagy of mitochondria. The aim of this study was to examine the effect of an intensified training load on skeletal muscle mitochondrial quality control in relation to changes in mitochondrial oxidative capacity, maximal oxygen consumption, and performance in highly trained endurance athletes. Elite endurance athletes (n = 27) performed high-intensity interval exercise followed by moderate-intensity continuous exercise 3 days per week for 4 wk in addition to their usual volume of training. Mitochondrial oxidative capacity, abundance of mitochondrial proteins, markers of autophagy, and antioxidant capacity of skeletal muscle were assessed in skeletal muscle biopsies before and after the intensified training period. The intensified training period increased several autophagy markers suggesting an increased turnover of mitochondrial and cytosolic proteins. In permeabilized muscle fibers, mitochondrial respiration was ~20% lower after training although some markers of mitochondrial density increased by 5%-50%, indicative of a reduced mitochondrial quality by the intensified training intervention. The antioxidative proteins UCP3, ANT1, and SOD2 were increased after training, whereas we found an inactivation of aconitase. In agreement with the lower aconitase activity, the amount of mitochondrial LON protease that selectively degrades oxidized aconitase was doubled. Together, this suggests that mitochondrial respiratory function is impaired during the initial recovery from a period of intensified endurance training whereas mitochondrial quality control is slightly activated in highly trained skeletal muscle.